Facile growth of nickel foam-supported MnCo2O4.5 porous nanowires as binder-free electrodes for high-performance hybrid supercapacitors. (June 2022) - Chen, Huiyu; Du, Xuming; Liu, Xiaohong; Wu, Runze; Li, Yi; Xu, Chunju
Abstract: In this work, porous MnCo2 O4.5 nanowires (NWs) were directly grown on nickel foam (NF) via an initial hydrothermal route with an extra annealing treatment of precursor. Another comparative experiment was conducted with a lower amount of urea to obtain particle-based MnCo2 O4.5 films. These binder-free MnCo2 O4.5 @NF electrodes exhibited battery-type electro-chemical response with superior electro-chemical performance. Especially, the MnCo2 O4.5 -NWs@NF delivered a huge capacity of 288.47 C g −1 at 1 A g −1 and 78.07% of capacity retention at 10 A g −1 . Moreover, a hybrid supercapacitor (HSC) that was assembled using activated carbon (AC) as an anode could operate over a voltage of 1.7 V. The MnCo2 O4.5 -NWs@NF//AC HSC delivered an energy density of up to 29.57 W h kg −1 at the power density of 914.28 W kg −1, and it could still hold 20.82 W h kg −1 since the power density was improved to 8.24 kW kg −1 . In addition, both these MnCo2 O4.5 NWs- and films-based HSCs showed an impressive cyclic stability over continuous 6000 cycles at a high current density of 6 A g −1, but only a little capacity decay was observed. Such extraordinary electro-chemical performance makes the binder-free MnCo2 O4.5 -NWs@NF electrode material promising and very feasible to be applied for electro-chemical energy storage devices such as batteries, supercapacitors, and so on. Graphical abstract: Porous MnCo2 O4.5 nanowires (NWs) were directly grown on nickel foam (NF) via an initial hydrothermal route with an extra annealing treatment of precursor. The binder-free MnCo2 O4.5 -NWs@NF electrode exhibited battery-type electrochemical response with a huge capacity of 288.47 C g −1 at 1 A g −1 . The assembled MnCo2 O4.5 -NWs@NF//AC hybrid supercapacitor delivered a high energy density of 29.57 W h kg −1 at a power density of 914.28 W kg −1 . Unlabelled Image Highlights: Porous MnCo2 O4.5 nanowires on Ni foam were hydrothermally prepared. A highly specific capacity of 288.47 C g −1 at 1 A g −1 was obtained. The HSC device delivered an energy density of 29.57 W h kg −1 at 914.28 W kg −1 .